A Transforming Urban Social Conflict through the Reconciliation and Peace Village Program: A Quantitative Peacebuilding-Based Analysis in Manggarai Urban Village - Rulinawaty Rulinawaty; Lukman Samboteng (AGUSPATI Research Institute, 2026)
Abstract— Urban social conflict does not merely emerge as a security disturbance, but also as a multidimensional problem involving physical space, digital space, social relations, and the psychological condition of residents. This study aims to analyze the dynamics of social conflict in Manggarai Urban Village and formulate intervention priorities for the Reconciliation and Peace Village Program based on peacebuilding and conflict transformation approaches. The study uses a descriptive quantitative approach supported by quantified thematic analysis. Data were obtained from a survey of 84 residents of Manggarai Urban Village. Open-ended responses were coded into binary variables and then analyzed through frequency distributions, percentages, cross-tabulation by area, triangulation with mapping reports, and the construction of a risk or intervention priority index. The results show that the most dominant theme was trauma, fear, and anxiety at 90.5%, followed by social media or content at 84.5%, damage, injury, or victims at 77.4%, and provocation at 72.6%. These findings indicate that conflict in Manggarai cannot be reduced to physical brawls alone, but reflects social conflict shaped by digital provocation, economic pressure, weak family supervision, and the need for psychosocial recovery. Risk mapping shows that RW 012, RW 003, RW 004, and RW 005 are priority areas for intervention. This study concludes that the Reconciliation and Peace Village Program should be developed as an integrated intervention that combines environmental security, cyber patrols, mediation, youth empowerment, alternative education, family strengthening, and psychosocial recovery. The implication is that urban social conflict prevention models must be data-driven, collaborative, and oriented toward positive peace.